2004
DOI: 10.1074/jbc.m407843200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Basis for the Affinity Maturation of a Camel Single Domain Antibody

Abstract: Affinity maturation of classic antibodies supposedly proceeds through the pre-organization of the reactive germ line conformational isomer. It is less evident to foresee how this can be accomplished by camelid heavychain antibodies lacking light chains. Although these antibodies are subjected to somatic hypermutation, their antigen-binding fragment consists of a single domain with restricted flexibility in favor of binding energy. An antigen-binding domain derived from a dromedary heavy-chain antibody, cAb-Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 32 publications
1
45
1
Order By: Relevance
“…In contrast to our findings, a previous detailed study of a virus-neutralizing Ab using engineered mutations selected for affinity suggested that improvements in the on-rate enhanced neutralizing activity (18). Abs directed against some model Ags that have been characterized previously at a kinetic level also show an importance of the off-rate in affinity maturation caused by somatic mutations (14,15,17,37,38).…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to our findings, a previous detailed study of a virus-neutralizing Ab using engineered mutations selected for affinity suggested that improvements in the on-rate enhanced neutralizing activity (18). Abs directed against some model Ags that have been characterized previously at a kinetic level also show an importance of the off-rate in affinity maturation caused by somatic mutations (14,15,17,37,38).…”
Section: Discussioncontrasting
confidence: 55%
“…However, the degree to which different organisms rely on the fine-tuning conferred through somatic hypermutation appears to somewhat of a ''sliding scale.'' According to recent publications, the camel single-domain VHH repertoire seems structurally limited (30), so low-( M) affinity binders are selected from the primary repertoire, and mutation is required to significantly (1,000-fold) improve binding affinity (11). In contrast, the study of an IgNAR V-region family presented here demonstrated that high-affinity (nM) binders could be selected directly from the primary repertoire.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, little is known of how singledomain antibody fragments, which lack one of the V domains, are matured. A study of an anti-hen egg-white lysozyme (HEL) camel heavy-chain antibody variable (VHH) domain in its germ line and mutated form showed that, despite the lack of binding-site plasticity conferred by pairing with a second domain and the presence of a complementarity-determining region (CDR)3-constraining disulphide bond, a 300-fold increase in binding affinity was achieved by increasing VHH-antigen complementarity and apolar buried surface area (11). However, all but one of the clones in the study were generated in vitro and, so, tell little of how the antigen-stimulated repertoire is generated.…”
Section: First Molecular and Biochemical Analysis Of In Vivo Affinitymentioning
confidence: 99%
“…Thus, although Nb592 itself might not directly be used as a clinical inhibitor, it provides a template for the future development of this type of molecular scaffold. Several techniques may also be applied to improve the binding affinity of Nb592 (31).…”
Section: Discussionmentioning
confidence: 99%